Analysis of the genomic architecture of a complex trait locus in hypertensive rat models links Tmem63c to kidney damage - Schulz, Angela; Müller, Nicola Victoria; van de Lest, Nina Anne; Eisenreich, Andreas; Schmidbauer, Martina; Barysenka, Andrei; Purfürst, Bettina; Sporbert, Anje; Lorenzen, Theodor; Meyer, Alexander M; Herlan, Laura; Witten, Anika; et al. (eLife, 2019)
Unraveling the genetic susceptibility of complex diseases such as chronic kidney disease remains challenging. Here, we used inbred rat models of kidney damage associated with elevated blood pressure for the comprehensive analysis of a major albuminuria susceptibility locus detected in these models. We characterized its genomic architecture by congenic substitution mapping, targeted next-generation sequencing, and compartment-specific RNA sequencing analysis in isolated glomeruli. This led to prioritization of transmembrane protein Tmem63c as a novel potential target. Tmem63c is differentially expressed in glomeruli of allele-specific rat models during onset of albuminuria. Patients with focal segmental glomerulosclerosis exhibited specific TMEM63C loss in podocytes. Functional analysis in zebrafish revealed a role for tmem63c in mediating the glomerular filtration barrier function. Our data demonstrate that integrative analysis of the genomic architecture of a complex trait locus is a powerful tool for identification of new targets such as Tmem63c for further translational investigation.
Keywords: albuminuria; blood pressure; next generation sequencing; RNA sequencing; rat; zebrafish